Public and private hospitals in Bangladesh: service quality and predictors of hospital choice - Andaleeb, Syed Saad (© 2000 Published by Oxford University Press, 2016)
This article was published in the Health Policy Planning [© 2000 Published by Oxford University Press] and the definite version is available at: http://doi.org/10.1093/heapol/15.1.95 The Journal's website is at: http://heapol.oxfordjournals.org/content/15/1/95